Sur le potentiel génératif d’une acquisition associée aux arts vivants - Larocque, Gabrielle (Muséologies)

(untitled) (Association Québécoise de Promotion des Recherches Étudiantes en Muséologie (AQPREM), 2026)
The close of the 2010s saw the acquisition of several works of the Quebec choreographer Paul-André Fortier by various cultural institutions. These acquisitions took the form of scenic elements, plans or audio and visual documentation. In 2020, the work Bras de plomb (1993), the result of a collaboration with the artist Betty Goodwin, was acquired by the Mackenzie Art Gallery (MAG), which received all the costumes and sets. At the time of the donation, the choreographer, as the donor, shared his desire to see these elements “used,” and the MAG was to take him at his word, presenting the elements as objets d’art, sources of inspiration and even, actual scenography supporting re-creations. Shaped by Goodwin’s creative thinking, the scenic elements of Bras de plomb are works in themselves that the MAG could place alongside other works - sculptures and drawings - by the Canadian artist already in its collection.Informed by the concept of authorized heritage discourse (AHD) derived from critical heritage studies, the example of Bras de plomb collected by the MAG and activated through partnerships with the performing arts milieu, illustrates the articulation of different modes of knowledge production based on the generative potential of an acquisition associated with the performing arts. Everything suggests that it is the fundamental components of this specific heritage (material, immaterial and performative) that lead inevitably to an encounter between forms of expertise, giving rise to interdisciplinary practices that can be approached as acts of heritage. How are these fundamental components connected to the challenges that this type of heritage pose for cultural institutions? Why do they impel these institutions to integrate expertise from outside the boundaries of AHD, and what impact does the integration of this expertise have on knowledge production? Finally, do these acts of collaboration supports the institution’s semantic and confirmatory role (Boltanski, 2008)? The fundamental components that constitute the heritage of performing arts function in this exploration as a heuristic framework for examining the generative potential of museum collection components associated with the performing arts, creating a relational space where multiple points of view collaborate in articulating knowledge stored within the work. It is this interdisciplinary process that seems to support the collective value of these components and, potentially, the heritage value of the choreography. This essay thus contributes both to theorizing the fundamental components of memory for the performing arts and to reporting on collaborative curatorial practices activating a collection in a Canadian art museum.